Structural characterization of SnS thin films prepared by vacuum evaporation technique - Ganesha Antarnusa (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2024)
Tin Sulfide (SnS) thin films were fabricated using vacuum evaporation techniques under a pressure of approximately 2×10⁻⁵ mbar. Cleaned microscope glass substrates were utilized, with a substrate temperature maintained at 300 K. The deposition of the SnS thin films was conducted by placing spacers between the substrate and the source at distances of 10 cm, 15 cm, and 25 cm. The study of SnS thin films included X-ray diffraction (XRD), scanning electron microscope (SEM), and energy dispersive analysis X-ray (EDX). The XRD patterns of the SnS thin films revealed good crystallization and confirmed the presence of an orthorhombic crystal structure with lattice parameters for sample 1 (10 cm spacer): a = 4.308 Å, b = 11.142 Å, c = 4.132 Å; sample 2 (15 cm spacer): a = 4.305 Å, b = 11.101 Å, c = 4.217 Å; and sample 3 (25 cm spacer): a = 4.081 Å, b = 11.135 Å, c = 4.292 Å. The preferred orientation was along the (0 4 0) planes for all films. Lattice parameters, grain size, and microstrain in the films were calculated from XRD patterns and correlated with the substrate spacer. Grain size distributions were derived from SEM micrographs, revealing a grain size of approximately 0.5 μm. EDX analysis indicated the chemical composition of the sample, with elements Sn = 37.86% and S = 13.58%.